Meningkatkan Pengetahuan dan Praktik Ibu dalam Pemberian Makanan Pendamping ASI melalui Metode Demonstrasi Emosional: Enhancing Maternal Knowledge and Practices in Complementary Feeding through Emotional Demonstration Methods - Intiyati, Ani; Edi, Imam Sarwo; Soesanti, Inne; Christianingsih, Juliana; Suprihatin, Kusmini; Widarti, Luluk (Universitas Airlangga, 2024)
Background: Complementary feeding is crucial for children's growth and development, especially between the ages of 6 to 24 months. Adequate nutritional intake during this period can prevent long-term health issues, such as stunting and obesity. However, many mothers struggle with providing appropriate complementary feeding due to a lack of knowledge and inappropriate feeding practices. Objectives: This study aimed to assess the effectiveness of the Emotional Demonstration (Emo Demo) method in improving maternal knowledge, attitudes, and behaviors related to complementary feeding. Methods: Using a pretest-posttest control group design, 100 mothers with children aged 6 to 24 months were assigned to one of three groups: control (lecture), demonstration, and Emo Demo. Data were collected via questionnaires and observational assessments at multiple intervals to measure the sustainability of behavior changes. Statistical analyses, including ANOVA and Least Significant Difference (LSD) tests, revealed that the Emo Demo method significantly enhanced knowledge, attitudes, and feeding practices compared to traditional methods. Results: The study found no significant demographic differences between groups. ANOVA showed significant improvements in knowledge, attitudes, and behavior (p-value<0.05). LSD analysis revealed significant changes in the Emo Demo group (p-value=0.010 for knowledge and behavior, p-value=0.028 for attitude), indicating its effectiveness in improving complementary feeding practices. Conclusions: Innovative and emotionally engaging methods like Emo Demo can effectively address the challenges of complementary feeding, ultimately contributing to public health efforts to reduce stunting in Indonesia. Further research is recommended to refine educational strategies for improving maternal nutrition practices in diverse communities.